Angiosarcoma in Spleen - A Case Report - Rahman, Md Mustafizur; Kutubi, Afroza; Ghosh, Dilip Kumar; Rahim, Abdur; Alam, Jahangir; Hossain, AZM Mostaque (Bangladesh Journal of Anatomy, 2011)
Primary angiosarcoma of the spleen is a rare neoplasm with a very poor prognosis. We present here computed tomography and magnetic resonance imaging of a 65-year-old man with primary splenic angiosarcoma The literature on primary splenic angiosarcoma is reviewed and imaging variability of this rare tumor is discussed. Mr. Hazi Abul Kalam, 65 years non-diabetic normotensive got admitted in Shaheed Suhrawardy medical college hospital with the complaints of anorexia with marked weight loss for last 1 year and feeling of a lump in left upper abdomen for last 10 months. On abdominal examination spleen was enlarged in long axis 10 cm from left costal margin, non tender, margin regular, firm in consistency and all others examinations revealed normal. Ultrasonography reveals cholelithiasis with space occupying lesion in spleen otherwise normal study. FNAC of spleen no malignant cell or caseation necrosis but TB can not be excluded. Computed tomography (CT) scan of abdomen and CT guided FNAC shows adeno carcinoma of spleen. After consultation with oncologist laparotomy & spleenectomy done. Histopathology shows angiosarcoma. Patient were referred to oncologist for further management. Keywords: Spleen; Angiosarcoma; Computed Tomography; Magnetic Resonance Imaging. DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8151 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 59-62